Riccia melitensis Mass. (Marchantiophyta: Ricciaceae), an endemic species of the Maltese archipelago? - Vincent, Hugonnot (Phytotaxa, 2015)
Riccia melitensis was considered to be an andemic species of the Maltese Archipelago and has never been relocated in the field since its discovery in 1913. The type specimen of Riccia melitensis Mass. has been examined and its taxonomic morphological characters re-evaluated. As a result, R. melitensis is considered to be a synonym of R. ciliifera Lindenb.